Comparison of Mitochondrial Reactive Oxygen Species Production of Ectothermic and Endothermic Fish Muscle - Wiens, Lilian; Banh, Sheena; Sotiri, Emianka; Jastroch, Martin; Block, Barbara A.; Brand, Martin D.; Treberg, Jason R. (Frontiers in Physiology, 2017)
Recently we demonstrated that the capacity of isolated muscle mitochondria to produce reactive oxygen species, measured as H2O2 efflux, is temperature-sensitive in isolated muscle mitochondria of ectothermic fish and the rat, a representative endothermic mammal. However, at physiological temperatures (15C and 37C for the fish and rat respectively), the fraction of total mitochondrial electron flux that generated H2O2, the fractional electron leak (FEL), was far lower in the rat than in fish. Those results suggested that the elevated body temperatures associated with endothermy may lead to a compensatory decrease in mitochondrial ROS production relative to respiratory capacity. To test this hypothesis we compare slow twitch (red) muscle mitochondria from the endothermic Pacific bluefin tuna (Thunnus orientalis) with mitochondria from three ectothermic fishes (rainbow trout (Oncorhynchus mykiss), common carp (Cyprinus carpio) and the lake sturgeon (Acipenser fulvescens)) and the rat. At a common assay temperature (25C) rates of mitochondrial respiration and H2O2 efflux were similar in tuna and the other fishes. The thermal sensitivity of fish mitochondria was similar irrespective of ectothermy or endothermy. Comparing tuna to the rat at a common temperature, respiration rates were similar, or lower depending on mitochondrial substrates. FEL was not different across fish species at a common assay temperature (25C) but was markedly higher in fishes than in rat. Overall, endothermy and warming of Pacific Bluefin tuna red muscle may increase the potential for ROS production by muscle mitochondria but the evolution of endothermy in this species is not necessarily associated with a compensatory reduction of ROS production relative to the respiratory capacity of mitochondria.